184. Implementation and Evaluation of an Electronic Antimicrobial Prior Authorization Approval Process at a Large Academic Medical Center. (26th November 2018) - Mehta, Jimish; Olson, Jonathan; Ketcherside, W Joseph; Hunt, Lauren; Palermo, Brandon; Hamilton, Keith
Abstract: Background: Prior authorization (PA) of antimicrobial agents is recommended by CDC as a core antimicrobial stewardship (AMS) intervention and has been a cornerstone of the Hospital of the University of Pennsylvania (HUP) AMS program since its inception. Previously, prescribers called the PA pager, waited for a callback, discussed the case with the AMS team, and received approval or an alternative recommendation. The objective of this study was to implement a new electronic prior authorization approval platform within existing clinical decision support software (CDSS) and evaluate its utilization. Methods: Electronic PA was introduced to HUP prescribers in January 2017. At the point of order entry for a restricted agent, an approver's name is a required field. In the CDSS, the request is initiated by selecting the patient and indication for use. The next screen displays additional risk factors to select and auto-populates the patient's current and historic cultures. The requestor selects the relevant cultures and desired antimicrobial(s), enters contact information, and submits the request. Review and approval by AMS team are completed in the CDSS, often without requiring a phone call. Pharmacy views a log of requests to determine whether the name given on the order as approver is true. Process metrics were evaluated using a retrospective cohort study from January 2017 through December 2017. Results: There were 437 unique users of the PA system. Uptake over time is displayed in Figure 1. 1, 934 unique patients had 3, 329 requests submitted. The most frequent indications were for prophylaxis, other, and pneumonia. Levofloxacin was most commonly requested (36.76%, 1, 297 of 3, 528), followed by meropenem, caspofungin, and fluconazole. 88.7% (2, 952 of 3, 329) of overall requests approved. The frequency of PA requests by hour is presented in Figure 2. During AMS hours, the median time to response was 18 (8–42) minutes. 18.4% (649 of 3, 528) of requests were submitted during off hours. Conclusion: Based on user uptake and response times, electronic PA was successfully implemented at HUP. Software to facilitate PA shows promise to assist in facilitating PA and tracking relevant process metrics. Disclosures: J. Mehta, ILUM Health Solutions: Consultant, Salary. J. Olson, ILUM Health Solutions: Consultant, Salary. W. J. Ketcherside, ILUM Health Solutions: Consultant, Salary. L. Hunt, ILUM Health Solutions: Consultant, Salary. B. Palermo, ILUM Health Solutions: Employee, Salary.